Comparing the Efficacy of Ticagrelor and Clopidogrel in Patients with Acute Ischemic Stroke - Kashipazha, Davood; Rafie, Shahram; Ghanbari, Saeed; Alwanian, Maryam (Journal of Neonatal Surgery, 2025)
Introduction: This study compared the effects of using clopidogrel and ticagrelor for 90 days in reducing the risk of subsequent stroke or death and reducing related clinical symptoms, severe bleeding, and disability among patients with ischemic stroke. Methods: The study was conducted as a randomized controlled clinical trial among patients with ischemic stroke referred to Golestan Hospital, Ahvaz. Two groups of patients were included and divided into each group in a 1:1 ratio using a simple random allocation method. The two groups received ticagrelor or clopidogrel plus aspirin within 24 hours after the onset of symptoms for 30 days. The trial's outcome was the combined risk of major ischemic events at 90 days. It was measured by the mRS (Modified Rankin Score) criterion and the incidence of recurrent stroke. Results: In this study, 185 patients were studied in the ticagrelor + aspirin group and 187 in the clopidogrel + aspirin group. Comparing the two groups regarding the incidence of recurrent stroke at 90-day follow-up showed that the difference between the two groups was not significant, despite the higher percentage of recurrent stroke in the clopidogrel + aspirin group (9.1% vs. 7.0%) (P = 0.465). Comparing the two groups regarding stroke outcome based on the mRS criterion at 90-day follow-up revealed that the mean mRS in the clopidogrel + aspirin group was significantly lower (1.87 ± 1.67 vs. 2.37 ± 1.79; P = 0.005). Discussion and Conclusion: Based on the results, the two drug groups were not statistically significant regarding stroke outcomes. Since all cases of hemorrhagic transformation occurred in NIHSS ≥5, we should treat with caution in prescribing dual antiplatelet agents in these people.